Religion, National Identity and Nation Building: Muhammad Mitwalli Shaʿrawi's Concept of Islam and Its Ties to Modern Egyptian Politics. (18th March 2016) - Brinton, Jacquelene
Abstract : Muhammad Mitwalli Shaʿrāwī (1911–1998) was a Muslim religious scholar (s. ʿalim, p. ʿulamaʾ) who worked in an official capacity for the Egyptian government, and gained celebrity through his televised Quranic interpretations. By the time Shaʿrāwī began his television career, Al-Azhar, the premier institution for training Sunni ʿulamaʾ, was fully integrated into the apparatus of the Egyptian Republic, which made it easy for the state to solicit the help of ʿulamaʾ like Shaʿrāwī in its nation-building project. Shaʿrāwī used Islam to bring forth a new sense of belonging, but his language about national belonging clashed with his exclusivist religious language. By looking at the attempted construction of national identity over time, this article charts the negotiation between religion and politics in late twentieth century Egypt where religion was not ousted from public discussion, but was subject to institutionalized restrictions, and allowed continuities in order to support national inclusivity.